Does China’s outward direct investment improve the institutional quality of the belt and road countries? - Pan, Chunyang; Wei, William Xiaojun; Muralidharan, Etayankara; Liao, Jia; Andreosso-O'Callaghan, Bernadette (My University, 2020)
This article investigates the effects of China’s outward direct investment (ODI) on the institutional quality of the Belt and Road (B&R) countries. Based on a panel data set of 63 B&R countries during the period 2003 to 2016, we find that China’s ODI improves the institutional quality of B&R countries not only in the short run but also in the long run. Further, although China’s ODI exerts no differential impacts on host country institutional dimensions of “control of corruption,” “government effectiveness,” and “political stability” in countries with different natural resource endowments, it improves their institutional dimensions of “regulatory quality” and “rule of law,” implying that China’s ODI may help the host B&R countries minimize the “resource curse”. As one of the most important strategies for China’s opening-up development in the current era, the B&R initiative serves as means to promote sustainable development of B&R countries. The article therefore contributes to existing scholarship on the institutional effects of China’s ODI and sheds light on the mechanisms that drive sustainable development.
Keywords: outward direct investment; institutional quality; belt and road countries; China